If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M * 6 + m * 5 = 56 Reorder the terms for easier multiplication: 6M + m * 5 = 56 Reorder the terms for easier multiplication: 6M + 5m = 56 Solving 6M + 5m = 56 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-5m' to each side of the equation. 6M + 5m + -5m = 56 + -5m Combine like terms: 5m + -5m = 0 6M + 0 = 56 + -5m 6M = 56 + -5m Divide each side by '6'. M = 9.333333333 + -0.8333333333m Simplifying M = 9.333333333 + -0.8333333333m
| x^6+4x^2+3=0 | | -(m+8n-8)= | | 10-6v=114 | | 2y+18+36=9y-11-54 | | 6x^2-5x-40=0 | | 6r+3=4r-13 | | 8=4(y+6)-8y | | 5x+2(1-x)=2(2x+1) | | 265.74=52.00x+135.74 | | 3x+x=-3 | | .4x+6=10 | | 15+5x=9+1x | | 3x-7y=x | | 7x-10-2x=9x-7 | | -3=-10-5x | | 2(3x-7)-5=3-(4x-5) | | -3(-6+8)= | | -5x-5x=62-2 | | e(x)=x^2+8x-9 | | 105z=9-110 | | -12=6u+18-9u | | 5m-160-30m-120=2 | | 0.8a=7.5 | | 0.50x+0.10(60)=0.25(34) | | 4x+3=-6+2x+21 | | (5x-2)=7[x-(5x-2)] | | m^3+26m^2+169m= | | 3x^2y+2x=5(1-y) | | ((x*4-3*4))+8=92 | | -2(t-1)+5t=6t-3 | | 0.95x+0.5(12-x)=.10(24) | | 8x+28=16 |